Study of behavioral patterns and infection analyses in anopheline species involved in the transmission of malaria in Buriticupu and São José de Ribamar municipality, Maranhão State, Brazil - Barros, Vera Lúcia Lopes de; Costa, Fábio Medeiros da; Silva, Antônio Rafael da; Gonçalves, Eloisa da Graça Rosário; Bezerra, Denilson da Silva; Lorosa, Elias Seixas; Tadei, Wanderli Pedro (EntomoBrasilis, 2020)
Anopheles darlingi Root and Anopheles aquasalis Curry are the main vectors of malaria that occur in the State of Maranhão. Entomological surveys based on the behavior and infectivity of these vectors are important for the elaboration of disease control strategies. The objectives of this work were to study the behavioral patterns of mosquitoes, determining population and hematophagic peaks, dietary preferences, infectivity rate and characterization of breeding sites in two municipalities in the State of Maranhão: Buriticupu and São José of Ribamar. Larvae and pupae were collected in breeding sites and adult females in home environments. Mosquito behavior, their dietary preferences and Plasmodium spp infection rates were analyzed. The vegetation and physicochemical patterns in the breeding sites found are in agreement with those described for species from the Amazon region and the Brazilian Atlantic coast. Anopheles darlingi was the most prevalent mosquito in Buriticupu breeding and home environments. This species was found mainly fed on human blood and naturally infected with Plasmodium vivax Grassi & Feletti and Plasmodium falciparum Welch. Anopheles aquasalis was more frequent in breeding sites in São José de Ribamar, as well as in home environments, whose specimens were mainly fed with human and bird blood. The main peaks of mosquito occurrence in Buriticupu were between 6 pm to 9 pm and in São José de Ribamar we did not record a definite peak. In the first municipality A. darlingi showed dominance over Anopheles albitarsis Lynch Arribálzaga s.l., Anopheles oswaldoi Peryassú, Anopheles nuneztovari Gabaldón and Anopheles evansae Brèthes,, besides presenting a correlation with rainfall. In the second municipality, A. aquasalis was dominant over A. albitarsis s.l. and there was a correlation between these two species and the rainy season. We conclude that the collected data contribute to elucidate the dynamics of malaria transmission in the region and guide the control actions directed to the elimination of the disease in the country.